BUSINESS FEASIBILITY ANALYSIS REVIEWED FROM VARIOUS ASPECTS AT KENANGAN OUTDOOR BEKASI - Sugiarti; Jumiyati; Maria Lapriska Dian Ela Revita; Rina Oktiyani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of establishing Kenanga Outdoor is to facilitate and facilitate people who want to do outdoor activities. Kenanga Outdoor is a solution for those who have the view that outdoor activities are difficult, especially in terms of equipment preparation. This study aims to determine the feasibility of establishing an outdoor equipment rental business in Kenanga Outdoor by analyzing various relevant and fundamental aspects in the business world. Specifically, the objectives of this study are as follows: 1. Analyze market aspects to determine potential demand, consumer characteristics, market segmentation, and the level of competition in the outdoor equipment rental industry in the target business area. 2. Evaluate technical aspects related to business operations, such as business location, types of equipment rented, human resource needs, and distribution and customer service systems. 3. Financial aspects that include initial capital requirements, operational cost projections, income estimates, break-even point calculations, and return on investment. 4. Review legal and environmental aspects, including business licensing, compliance with government regulations, and the impact of business operations on the surrounding environment. 5. Environmental Aspect (Green Business) 6.. Environmental Impact Analysis Aspect (AMDAL) 7. Social Media and Promotion Aspect. Then assess the overall feasibility of the business based on the results of the analysis of each aspect, in order to be the basis for decision making in establishing and developing the Kenanga Outdoor outdoor equipment rental business.